Aerogen bonds formed between AeOF2 (Ae = Kr, Xe) and diazines: comparisons between σ-hole and π-hole complexes. Issue 7 (18th January 2018) - Zierkiewicz, Wiktor; Michalczyk, Mariusz; Scheiner, Steve
Abstract : AeOF2 (Ae = Kr, Xe) engages in noncovalent aerogen bonds with diazines, of both σ-hole and π-hole type. The former are particularly stable, several times stronger than typical H-bonds. Abstract : The interaction between KrOF2 or XeOF2 and the 1, 2, 1, 3, and 1, 4 diazines is characterized chiefly by a Kr/Xe⋯N aerogen bond, as deduced from ab initio calculations. The most stable dimers take advantage of the σ-hole on the aerogen atom, wherein the two molecules lie in the same plane. The interaction is quite strong, as much as 18 kcal mol −1 . A second class of dimer geometry utilizes the π-hole above the aerogen atom in an approximate perpendicular arrangement of the two monomers; these structures are not as strongly bound: 6–8 kcal mol −1 . Both sorts of dimers contain auxiliary CH⋯F H-bonds which contribute to their stability, but even with their removal, the aerogen bond energy remains as high as 14 kcal mol −1 . The nature and strength of each specific interaction is confirmed and quantified by AIM, NCI, NBO, and electron density shift patterns. There is not a great deal of sensitivity to the identity of either the aerogen atom or the position of the two N atoms in the diazine.